Transformation of Values, Identities & Life Styles at Iranian Society in Cinema Narration - Jamal Mohammadi; Abdollah Bicheranlo (Taḥqīqāt-i Farhangī-i Īrān)
This article is to do a sociologically analysis on transformation of values, Identities and life styles at Iranian post Islamic revolution society in cinema narrations. The method of study is qualitative; first the selected movies have been analyzed by applying semiotic narration analysis based on elements such as images, shots, actions, mise en secene, dialogues and scenes. Then their main social categories have been extracted and sociologically analyzed through thematic analysis strategy based on theoretical foundation of research. The population of research includes all post revolution Iranian cinema movies which 12 movies have been selected by purposive sampling method. These movies include; Narges, Fair People Wedding, Glass Agency, Under City Cover, Protest, Blue Scarf, Hemlock, Boutique, Wednesday Celebration, Trial in Street, about Eli & Separation of Nader & Simin. Findings show that selected movies narrate gaps, distinctness of social life domains, of instrumental rationality expansion & split of value systems